Wayward lives, beautiful experiments : intimate histories of riotous black girls, troublesome women and queer radicals - Hartman, Saidiya V. (London : Profile Books, 2021)
"In wrestling with the question, "What is a free life?" many young black women created forms of intimacy and kinship indifferent to the dictates of respectability, and outside the bounds of law. They cleaved to and cast off lovers, exchanged sex to subsist, and revised the meaning of marriage. Longing and desire fueled their experiments in how to live. They refused to labor like slaves or to accept degrading conditions of work. Beautifully written, Wayward Lives narrates the story of this radical transformation of black intimate and social life. It re-creates the experience of young black women who desired an existence qualitatively different than the one that had been scripted for them, and, for the first time, credits them with shaping a cultural movement that transformed the urban landscape. Through a melding of history and literary imagination, Wayward Lives seeks to recover the radical aspirations and insurgent desires of these young women."--Provided by publisher.
Includes bibliographical references and index.
Keywords: African American young women -- Social conditions -- 19th century; African American young women -- Social conditions -- 20th century; African American young women -- Sexual behavior -- History; Single women -- United States -- Social conditions -- 19th century; Single women -- United States -- Social conditions -- 20th century; Urban women -- United States -- Social conditions -- 19th century; Urban women -- United States -- Social conditions -- 20th century; Sex customs -- United States -- History; Prostitution -- United States -- History